Empowerment of Village Communities Through the Development of MSMES Based on Mosquito Spray Products - Ray, Aina ul Mardiyah; Nurhanifah, Nurhanifah; Harahap, Indra Naposo; Aulia, Icha Natasya; Siregar, Sastri Dalila; Azahra, Zelma (LPPPIPublishing, 2024)
This research explores strategies for empowering village communities through the development of Micro, Small and Medium Enterprises (MSMEs) with a focus on anti-mosquito spray products. The aim of this research is to increase the economic capacity and production skills of village communities through sustainable MSME initiatives. The methods used include technical training on making anti-mosquito spray, providing equipment and raw materials, as well as marketing support to expand market reach. It is hoped that the results of this program will increase the income and welfare of village communities, as well as provide solutions to health problems caused by mosquitoes. By empowering village communities through the development of MSMEs, it is hoped that economic independence will be created and a sustainable quality of life will be improved.